Rural small and medium enterprise: Information and communication technology as panacea - Olukayode, Obadun Mathew; Sheik Osman, Wan Rozaini; Hussein, Husam Abdulhameed; Ismael, Ahmed Naser; Masoud, Ahmed Abdulla; Mansor, Abdul Ghafar (2014)
Though, there are variations in the definitions of small and medium enterprises but it can be generally accepted as business activities that employ the services of 150 or fewer people in its activities and attributed with no link to the public limited company.Among the challenges facing the prospect of small and medium enterprise in the rural areas is the lack of integrating information and communication technology skills or strategies into their practice. Therefore, this paper engages the exploration of previous literatures in finding the benefits of information and communication technology to the rural small and medium enterprise.